2003
DOI: 10.1046/j.1600-6143.2003.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Risk of Recidivism in Methadone-Dependent Patients Undergoing Liver Transplantation

Abstract: Cirrhosis resulting from hepatitis C virus is presently the most common indication for liver transplantation (OLT) in the United States. A number of U.S. transplant centers require cirrhotics who are using methadone to discontinue it before proceeding with OLT. We sought to examine the outcomes of those patients who had undergone OLT at the Mount Sinai Medical Center.A retrospective chart review of 36 subjects on methadone maintenance treatment (MMT), and off heroin, at the time of OLT was performed.The median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 13 publications
(14 reference statements)
1
40
1
1
Order By: Relevance
“…Selection standards vary as well in regard to advanced age, history of alcohol abuse, and body mass index (6 -9). Some centers do not accept patients on maintenance methadone although there are favorable reports for outcome and a small risk for relapse among recipients on chronic methadone maintenance after transplantation (10,11). There has been similar success among patients with manageable psychotic disorders (12).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Selection standards vary as well in regard to advanced age, history of alcohol abuse, and body mass index (6 -9). Some centers do not accept patients on maintenance methadone although there are favorable reports for outcome and a small risk for relapse among recipients on chronic methadone maintenance after transplantation (10,11). There has been similar success among patients with manageable psychotic disorders (12).…”
Section: Patient Selectionmentioning
confidence: 99%
“…alcohol). Patients who are on stable methadone maintenance programmes are not excluded from transplant and can continue on such programmes after the transplant [22]. Finally, HIV-infected patients must show an appropriate degree of social stability to ensure adequate care in the posttransplant period.…”
Section: Virological Criteriamentioning
confidence: 99%
“…Studies have also shown that in general there is no difference in the MMT liver transplant recipients and general transplant population with regards to adherence to immunosuppressive medications and overall graft survival rates. 26,29,30 Hence such patients should be evaluated on a case to case basis and methadone can be safely continued in the post-transplant period in the usual doses. Those patients who are on stable adequate doses of methadone, follow other measures of MMT program and have excellent social support should be considered for liver transplant.…”
mentioning
confidence: 99%